2014
DOI: 10.1017/s0269889714000052
|View full text |Cite
|
Sign up to set email alerts
|

Producing Standards, Producing the Nordic Region: Antibiotic Susceptibility Testing, from 1950–1970

Abstract: ArgumentDuring the 1950s it became apparent that antibiotics could not conquer all microbes, and a series of tests were developed to assess the susceptibility of microbes to antibiotics. This article explores the development and standardization of one such testing procedure which became dominant in the Nordic region, and how the project eventually failed in the late 1970s. The standardization procedures amounted to a comprehensive scheme, standardizing not only the materials used, but also the methods and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…1 In the case of Europe and North America, historians have shown that distinct national antibiotic usage patterns have become socially entrenched over decades. [77][78][79][80][81] To this day, antibiotic usage patterns vary across Europe and North America despite both regions' close economic, political and cultural ties. 82 83 Differences of usage are even more substantial between HICs and LMICs with patients in the latter countries often depending to a much stronger degree on the efficacy BMJ Global Health of a limited number of locally available, affordable and easily administrable drugs-particularly in areas where there is no access to professional healthcare facilities.…”
Section: Prioritisationmentioning
confidence: 99%
“…1 In the case of Europe and North America, historians have shown that distinct national antibiotic usage patterns have become socially entrenched over decades. [77][78][79][80][81] To this day, antibiotic usage patterns vary across Europe and North America despite both regions' close economic, political and cultural ties. 82 83 Differences of usage are even more substantial between HICs and LMICs with patients in the latter countries often depending to a much stronger degree on the efficacy BMJ Global Health of a limited number of locally available, affordable and easily administrable drugs-particularly in areas where there is no access to professional healthcare facilities.…”
Section: Prioritisationmentioning
confidence: 99%
“…The main framework of this system was established already in 1928. Key features of the system were shared with the other Nordic countries, whose drug laws are routinely cited as the earliest of their kind . It established the principle that a drug had to be approved of before it could be legally sold—that is, preapproval, also referred to as registration, market authorization, or licensing.…”
Section: Context Of Origin: Containing “A Flood Of Drugs”mentioning
confidence: 99%
“…Drug resistance had become a significant issue by that time, at least among some biomedical researchers in the US, Norway and Japan, and would continue to increase in significance, intensifying warnings, research interest and funding to combat resistance as a phenomena produced by drug use both in the microbiological laboratory and the clinic (Creager, 2007;Gradmann, 2011;Lie, 2014;Podolsky, 2010Podolsky, , 2014. But according to Lederberg's interpretation, presented in Stockholm in May 1959, the cell was killed by these substances before they accessed chromosomes and become mutagenic.…”
Section: Transits Of the Bacterial Cell Wallmentioning
confidence: 99%
“…On the history of drug patenting seeGaudillie`re (2008),Romero de Pablos (2011, 2014 andHu¨ntelmann (2012).2 A staining technique designed by H.C. Gram in the late 1880s, combined crystal violet dye and an iodine salt as a mordant to fix the dye. The technique divided cells into those that were tainted by this combination and those that were not.…”
mentioning
confidence: 99%